Photoinduced underwater superoleophobicity of TiO2 thin films - Sawai, Yusuke (Langmuir : the ACS journal of surfaces and colloids, 2013)
The photoinduced wettabilities of water, n-hexadecane, dodecane, and n-heptane on a flat TiO2 surface prepared by a sol-gel method-based coating were investigated. An amphiphilic surface produced by UV irradiation exhibited underwater superoleophobicity with an extremely high static oil contact angle (CA) of over 160°. The TiO2 surface almost completely repelled the oil droplet in water. A robust TiO2 surface with no fragile nanomicrostructure was fabricated on a Ti mesh with a pore size of approximately 150 μm. The fabricated mesh was found to be applicable as an oil/water separation filter